The Development of Thermal Expansion Practicum Sets to Improve Science Process Skills of High-School Students - Solihan Solihan; I Made Astra; Esmar Budi (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2018)
This study aims to develop thermal length expansion practicum sets that are expected to improve high-school science process skills (SPS) in expansion material on metal rods. This research was conducted at SMAN 2 Bekasi in class XI by comparing the control and the experimental class. This study uses the ADDIE approach to analyze, design, develop, implement, and evaluate the thermal expansion length practicum sets. The feasibility test of this practicum sets was carried out in two ways: conducting experiments and validating tests from experts. The experimental results for the linear expansion coefficient of an iron bar are 3.09%, the brass is 5.81%, and the aluminum is 7.39% from the reference value. All of the experimental data still below the error acceptance level which is below 10%. The validation results give 85.5% from media experts and 86.1% from material experts. The trials on users obtained 93.9% of teachers and 85.4% of students. The N-gain in control and experiment class then compared to see the increase in SPS in each category. There was an increase in the experimental class SPS value 7.3% higher than the control class, where the SPS value in the experimental class increased by 47.8%. Therefore, it can conclude that the thermal expansion practicum sets is feasible to use and can improve the science process skills of high school students.